Optimizing The Role of Accounting in Improving the Effectiveness of Tourism Destination Management - WIJAYA, Jesslyn San; APRILLIA, Ni Kadek; PRATIWI, Ni Komang Nadia; PRATAMA, Gusti Made Panji Dwi (Journal Management and Hospitality, 2024)
The tourism sector is one of the main pillars of economic growth in various countries, including Indonesia. To improve the competitiveness and sustainability of tourism destinations, effective management is a crucial aspect to consider. One of the key elements that can support this effectiveness is the optimal application of accounting. Accounting plays a role not only as a tool for recording financial transactions but also as a provider of relevant information for planning, controlling, and evaluating the performance of tourist destinations. This study aims to investigate how optimizing the role of accounting can enhance the effectiveness of tourism destination management. The method used in this study is a literature review, which involves examining various sources of literature, including scientific journals, books, and related research reports. The study's results demonstrate that integrating financial accounting, managerial accounting, and cost accounting can enhance the management of tourism destinations, improve resource utilization efficiency, and support strategic decision-making. Thus, optimizing the role of accounting significantly contributes to increasing the effectiveness of tourism destination management and is recommended as the primary focus in developing a sustainable tourism sector.